2010
DOI: 10.4319/lo.2010.55.6.2549
|View full text |Cite
|
Sign up to set email alerts
|

Roles of phosphorus and ultraviolet radiation in the strength of phytoplankton‐zooplankton coupling in a Mediterranean high mountain lake

Abstract: Ultraviolet solar radiation (UVR) and atmospheric nutrient inputs associated with aerosols are major worldwide stressors that simultaneously affect species and the interaction among them. A 2 3 5 field experimental design was used to determine how variations in light regimes (presence and absence of UVR [+UVR and 2UVR]) and nutrients might influence the strength of phytoplankton-zooplankton coupling (PZC). We observed unimodal curves for zooplankton biomass in response to increased food supply from nutrient en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…This study is part of a long-term in situ experiment designed to examine how the interaction of global-change stressors (UVR × P loads) affects the entire pelagic food web in a model ecosystem. The responses of algal and zooplanktonic compartments are described elsewhere [12], [14], [27], while here we report the dynamics and response patterns of the HMFW, which reveal noteworthy ecological mechanisms and implications.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…This study is part of a long-term in situ experiment designed to examine how the interaction of global-change stressors (UVR × P loads) affects the entire pelagic food web in a model ecosystem. The responses of algal and zooplanktonic compartments are described elsewhere [12], [14], [27], while here we report the dynamics and response patterns of the HMFW, which reveal noteworthy ecological mechanisms and implications.…”
Section: Introductionmentioning
confidence: 70%
“…[32]), reports how an entire HMFW responded to the joint impact of UVR and a P-load gradient which encompassed current and expected future scenarios of atmospheric dust deposition. The large spatial and temporal scales of the experimental set up allowed us to compile realistic information on entire trophic web dynamics [27] and infer their underlying ecological mechanisms through statistical analysis applied in mesocosm studies when experimental units could not be replicated [12], [44], [47][49]. Although the frequency at which the mesocosms were sampled precludes a detailed analysis for some compartments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, persistence of high winds would counteract this effect (depending on the strength of the pycnocline) by increasing the epilimnion depth and also by distributing particles/nutrients transported via the atmosphere (Escudero et al, 2005;Bullejos et al, 2010) and into the water column (i.e. nutrients reaching different depths due to vertical mixing transport).…”
Section: Discussionmentioning
confidence: 99%
“…6A,B in Bullejos et al 2010). The negative relationship between copepod abundance and atmospheric inputs in concert with the higher capacity of Daphnia to exploit the high seston levels strongly suggest that changes in the intensity and frequency of aerosols could substantially affect zooplankton community structure facilitating the establishment of cladocerans and rotifers more susceptible than copepods to growth limitation by sestonic C and mineral P, respectively.…”
Section: Speciesmentioning
confidence: 99%
“…A recent study showed how the combination of higher atmospheric depositions and the extreme UVR levels characteristic of high altitudes can strongly affect the strength of phytoplankton-zooplankton coupling in a high mountain lake (Bullejos et al 2010). The mechanisms behind these effects are however difficult to discern, as both quantity and quality of food for herbivorous grazers are simultaneously altered by these global factors.…”
mentioning
confidence: 99%